ANALISIS TOURISM DISTRIBUTION CHANNELS WISATAWAN MANCANEGARA PADA KAWASAN GREAT INDONESIA (Studi Pada Kawasan Great Batam, Provinsi Kepulauan Riau) - Mohamad Rizaldy; Supriono Supriono (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
The study, entitled Analysis of Tourism Distribution Channels International Tourists in Great Indonesia Region (Study on Great Area of Batam, Kepulauan Riau Province), aims to describe the attractiveness of the city of Batam to become a tourist destination for International tourists and to describe the strategy of tourism distribution channels applied in Batam City in attracting International tourists to visit the city of Batam. The type of research used is qualitative research with descriptive approach. The focus of this research is the tourism products that exist in the city of Batam that makes Batam interesting visited by international tourists and tourism distribution channels in the city of Batam. The research location is located in Batam City Region Kepulauan Riau Province. The research sites are located in the Office of Culture and Tourism of Batam City, ASITA (Association of Indonesian Tours and Travel Agencies), PT. Nusajaya Indofast and PT. Internusa Tour and Travel. Data Collection techniques in this study are observation, interview and documentation. Keywords: International Tourists, Distribution Channels, Tourism, Batam City АBSTRАK Penelitian yang berjudul Analisis Tourism Distribution Channels Wisatawan Mancanegara Pada Kawasan Great Indonesia (Studi Pada Kawasan Great Batam, Provinsi Kepulauan Riau), bertujuan untuk mendeskripsikan daya tarik Kota Batam sehingga menjadi tujuan wisata bagi wisatawan mancanegara (wisman) dan untuk mendeskripsikan strategi saluran distribusi pariwisata yang diterapkan di Kota Batam dalam menarik wisman untuk berkunjung ke Kota Batam. Jenis penelitian yang digunakan adalah penelitian kualitatif dengan pendekatan deskriptif. Fokus penelitian ini adalah produk-produk wisata yang ada di Kota Batam yang menjadikan Batam menarik dikunjungi oleh wisman dan saluran distribusi pariwisata wisman di Kota Batam. Lokasi penelitian bertempat di Daerah Kota Batam provinsi Kepulauan Riau. Situs penelitian berada di Kantor Dinas Kebudayaan dan Pariwisata Kota Batam, ASITA (Association of Indonesian Tours and Travel Agencies), PT. Nusajaya Indofast dan PT. Internusa Tour and Travel. Teknik pengumpulan data dalam penelitian ini adalah observasi, wawancara dan dokumentasi. Kаtа Kunci: Wisatawan Mancanegara, Saluran Distribusi, Pariwisata, Kota Batam